2021
DOI: 10.1001/jamapediatrics.2020.6371
|View full text |Cite|
|
Sign up to set email alerts
|

Association of the Timing of School Closings and Behavioral Changes With the Evolution of the Coronavirus Disease 2019 Pandemic in the US

Abstract: IMPORTANCEThe consequences of school closures for children's health are profound, but existing evidence on their effectiveness in limiting severe acute respiratory syndrome coronavirus 2 transmission is unsettled.OBJECTIVE To determine the independent associations of voluntary behavioral change, school closures, and bans on large gatherings with the incidence and mortality due to coronavirus disease 2019 . DESIGN, SETTING, AND PARTICIPANTSThis population-based, interrupted-time-series analysis of lagged indepe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 21 publications
0
25
0
Order By: Relevance
“…The benefit of school closure relative to other containment measures is unclear. A population-based study in the United States (U.S.) during a 60-day period beginning in March 2020, relative to baseline data beginning in January 2020, revealed a negative association of school closure with COVID-19 incidence and with COVID-19-related mortality, but the associations were stronger with voluntary behavioral changes (e.g., reduced time at the workplace and restaurant dining) than with school closure [ 10 ]. Using similar data and methodology, Auger and colleagues [ 11 ] also found that the incidence of COVID-19 and related mortality decreased with school closure, while Courtemanche and colleagues [ 12 ] found no association of school closure with the incidence of COVID-19 or with related mortality, but these studies failed to control for other voluntary behavior changes.…”
Section: Epidemiologic Considerations Of Covid-19 In Children and Implications For School Closurementioning
confidence: 99%
“…The benefit of school closure relative to other containment measures is unclear. A population-based study in the United States (U.S.) during a 60-day period beginning in March 2020, relative to baseline data beginning in January 2020, revealed a negative association of school closure with COVID-19 incidence and with COVID-19-related mortality, but the associations were stronger with voluntary behavioral changes (e.g., reduced time at the workplace and restaurant dining) than with school closure [ 10 ]. Using similar data and methodology, Auger and colleagues [ 11 ] also found that the incidence of COVID-19 and related mortality decreased with school closure, while Courtemanche and colleagues [ 12 ] found no association of school closure with the incidence of COVID-19 or with related mortality, but these studies failed to control for other voluntary behavior changes.…”
Section: Epidemiologic Considerations Of Covid-19 In Children and Implications For School Closurementioning
confidence: 99%
“…Children and youth are still severely affected by the COVID-19 pandemic, even though the acute phase of the disease is mostly mild in the young (1). They are over-proportionally affected by secondary consequences of the pandemic such as social deprivation, lack of physical activity, decrease in economic status, and dysconnectivity, especially in rural communities (2,3), and in countries like Germany, where closing of schools was not perceived as the last option in fighting the pandemic but as the first (4,5).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the contamination at school exists but is minor ( 13 , 14 ). Moreover, the prolonged closure of schools has resulted in adverse consequences for both children and their parents who work from home ( 15 , 16 ). All of these drawbacks were even greater in low-income families ( 17 ).…”
Section: Introductionmentioning
confidence: 99%